2017
DOI: 10.1111/jcmm.13322
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid down‐regulates NO and PGE2 expression viaMAPK pathway in rat chondrocytes

Abstract: Rosmarinic acid (RosA) is a water‐soluble polyphenol, which can be isolated from many herbs such as orthosiphon diffuses and rosmarinus officinalis. Previous studies have shown that RosA possesses various biological properties. In this study, we investigate the anti‐osteoarthritic effects of RosA in rat articular chondrocytes. Chondrocytes were pre‐treated with RosA, followed by the stimulation of IL‐1β. Real‐time PCR and Western blot were performed to detect the expression of matrix metalloproteinase (MMP)‐1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 33 publications
5
24
0
Order By: Relevance
“…In the present study, we found that IL-1β-induced expression of iNOS and COX2 were also attenuated by UA. Sox-9 is a vital transcription factor that positively regulates Collagen II synthesis and is indispensable for chondrocyte differentiation [36]. Our study further pointed out that UA obviously restored the levels of SOX9 inhibited by IL-1β treatment.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the present study, we found that IL-1β-induced expression of iNOS and COX2 were also attenuated by UA. Sox-9 is a vital transcription factor that positively regulates Collagen II synthesis and is indispensable for chondrocyte differentiation [36]. Our study further pointed out that UA obviously restored the levels of SOX9 inhibited by IL-1β treatment.…”
Section: Discussionsupporting
confidence: 66%
“…For OA, the active form of ERK, JNK and p38 was observed in synovial tissue and cartilage lesion. In addition, several lines of evidence understate that activation of MAPK induced by IL-1β trigger aggrecanases and MMPs-mediated articular cartilage degradation [36,39]. Specially, Therapy targeting p38 inhibitors could attenuate cartilage degeneration and relief pain in animal models [40].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced 5‐HT uptake exerted by gentisic acid in vitro (Cool, Leibach, Bhalla, Mahesh, & Ganapathy, ) could influence intracellular 5‐HT pool, as well. While rosmarinic acid and phloridzin demonstrated inhibitory effects on LDH and PGE2 levels, in multiple experimental paradigms of increased burden of inflammation and oxidative stress (Chen et al, ; Khalifa, Bakr, & Osman, ; Rocha et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Sprague Dawley rats (200‐250 g; 6 weeks old) were purchased from the Animal Center of Zhejiang University. Rat chondrocytes were prepared as described in previous studies . All animal studies were conducted in accordance with the Declaration of Helsinki, and the protocol was approved by the Ethics Committee of the 2nd Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, China.…”
Section: Methodsmentioning
confidence: 99%